ChemInform Abstract: Emerging Trends in Enzyme Inhibition by Multivalent Nanoconstructs. Issue 46 (November 2015) - Kanfar, Nasreddine; Bartolami, Eline; Zelli, Renaud; Marra, Alberto; Winum, Jean‐Yves; Ulrich, Sebastien; Dumy, Pascal
Abstract Review: 87 refs.